Understanding the body image perception of pregnant women during their third trimester in a tertiary care setting in Southern India - Ketaki Desai; Deepalaxmi Paresh Poojari; T.S. Shwetha; Rajani Upadhyaya; Preetha Ramachandra (BMC, 2024)
Abstract Background Pregnancy is a known physiological phenomenon characterized by various changes in the body. The physical and physiological changes that occur during pregnancy may impact the body image which may lead to implications such as body image issues or poor eating habits among pregnant women. This study aimed to analyze the body image perception of pregnant women in their third trimester. Methods This cross-sectional survey which involved the administration of a Multidimensional Body Self-Relations Questionnaire (MBSRQ), was conducted among pregnant women between 28 and 40 weeks of gestation in a tertiary care setting in Southern India. Descriptive statistics were used to report the demographic characteristics of the respondents. A one-sample t-test was used to analyze the difference between the present sample scores and the published norms of MBSRQ. Univariate Logistic Regression was done to find the association between the demographic variables and subdomains of MBSRQ. Results The mean age of the respondents (n = 246) was 29.5 years, and the period of gestation was 33.4 weeks. With mean scores of subscales of MSRQ as reference values, a greater proportion of women had higher scores on appearance orientation (52.44%), health evaluation (56.91%), and illness orientation (55.28%). Respondents scored less on appearance evaluation (52.03%) and body areas satisfaction scale (50.41%). The study found that pre-pregnancy BMI, abdominal circumference, and weight gain during pregnancy were associated with appearance orientation, overweight preoccupation, and self-classified weight. Health evaluation was associated with weight gain and Instagram use, while moderate-intensity physical activity during pregnancy was associated with higher health orientation. Conclusion Although pregnant women in our setting during the third trimester were oriented towards their appearance and considered themselves healthy and fit, almost half of the respondents reported dissatisfaction with their changing bodies and appearance. Self-reported physical activity status, body mass index, weight gain, level of education, use of Instagram app, and type of family were factors found to affect pregnant body image perception. Hence, we conclude that body image perception is affected during pregnancy, and healthcare professionals should be aware of this, and the factors associated with it while addressing the health of pregnant women. Clinical trial registration details The study was registered under the Clinical Trials Registry- India: CTRI/2023/08/056524. https://ctri.nic.in/Clinicaltrials/rmaindet.php?trialid=89771&EncHid=39880.12369&modid=1&compid=19 .